PENGEMBANGAN MODUL ELEKTRONIK RANCANGAN PENELITIAN PADA S1 PENDIDIKAN TEKNIK BANGUNAN FT UNJ - R. Eka Murtinugraha; Ridia Irin Imbatami; Riyan Arthur; Firros Hirzy; Mafie Musqyla (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2022)
The purpose of this research is to develop teaching material regarding research design in the Electronic Module-based Research Methodology course which consists of problems, theoretical basis, hypothesis submission, research methods and to find out the value of the effectiveness of electronic module teaching materials through limited distribution. This study uses a research and development research method (R&D) with the Thiagarajan 4D model. The results of the validation by material experts were 0,94 in the very high category, while the results of the validation by the media experts were 0,89 in the very high category. The limited trial results showed an increase in the average value of the pre test by 62,45 and post test by 78,53. Therefore, it can be concluded that the electronic module teaching materials for this electronic module can increase understanding in terms of material and are declared fit for use in learning.